Waking the Neighbours: Disruption of H-NS Repression by Overlapping Transcription - Wade, Joseph T. (Mol Microbiol, 2018)
The histone-like nucleoid structuring (H-NS) protein and its analogues bind large stretches of horizontally acquired AT-rich DNA in a broad range of bacterial species. Binding by H-NS silences the promoters within such DNA that would otherwise deplete the cellular pool of RNA polymerase. Selective de-repression can occur when sequence-specific DNA-binding proteins locally disrupt H-NS function; this mechanism is important for the regulation of many virulence genes. In this issue of Molecular Microbiology, Rangarajan and Schnetz show that when transcription from a neighbouring region invades an H-NS-bound locus, it can disrupt local H-NS repression. Moreover, they show that de-repression occurs in a dose-dependent manner, and they demonstrate a natural example of this in Escherichia coli. This finding has important implications for H-NS function and its impact on genome evolution.